Pengaruh Pemberian Jus Tomat Terhadap Tekanan Darah Pada Penderita Hipertensi di Kelurahan Mahawu Lingkungan II Kota Manado - Anggia Putri Utami Potabuga; Agust A. Laya; Irma M. Yahya (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Hypertension or high blood pressure is a condition when there is an increase in blood pressure, which is above 140 mmHg for istolic blood pressure and 90 mmHg for diastolic blood pressure.One of the therapies used to lower blood pressure is the administration of tomato juice because it is rich in lycopeine, potassium and bioflavonoids. The purpose of this study was to determine the effect of tomato juice on lowering blood pressure in hypertensive patients in Mahawu Village sub distrit II Manado City. The method used in this study is a design experiment with One Group pretest-postest design. The sample taken amounted to 15 respondents using purposive sampling. Data collection using SOPs and observation sheets. The collected data is processed using SPSS 16.0. Statistical test using Wilcoxon Test with a meaning level ( α) of 0.05. The results of the study using Wilcoxon statistical tests obtained the results of Systolic Pre-Post with a value of P value = 0.001 and Diastolic Pre-Post with a value of p Value = 0.002 where the value of p Value < α = 0.05). so that Ha was accepted and Ho was rejected so that there was an effect of giving tomato juice on lowering blood pressure in people with hypertension in Mahawu Village sub district II Manado City. The conclusion is based on the results of the study that there is an effect of giving tomato juice on reducing blood pressure in hypertensive patients in Kelurahan II Manado City.